(untitled) (Journal of Plant Disease Sciences, 2023)
Solvents, including acetone, chloroform, distilled water, ethanol, and methanol, were used to test the antibacterial capabilities of two plants, Psoralea corylifolia and Emblica officinalis, against Xanthomonas citri subsp. citri, the major cause of citrus canker disease. Psoralea corylifolia seed extract yielded the highest extraction yield (14.50%) in methanol and the lowest in dichloromethane (9.75%), whereas Emblica officinalis extract yielded the highest extraction yield (15.75%) in methanol and the lowest (0.65%) in petroleumether solvent. Psoralea corylifolia and Emblicaofficinalis methanol extracts were reported to have potential antibacterial action against Xanthomonas citri. In vitro screening of eight plant-concentration interactions revealed various levels of toxicity to the bacterium, indicated as mean zone of inhibition of bacterial growth. At all concentrations examined, it was found that E. officinalis plant extract inhibited the test bacterium the most when compared to P. corylifolia plantextract.